Design and development of wireless communication transceiver to support RFID reader at UHF band - Mohammad Shahrazel, Razalli; Mohd Azir, Mahdi, Prof. Madya Dr.; Alyani, Ismail, Dr.; Siti Mariam, Shafie; H., Adam (Brill Academic Publishers, 2011)
Link to publisher's homepage at http://www.brill.nl/